Transfer hydrogenation with abnormal dicarbene rhodium(iii) complexes containing ancillary and modular poly-pyridine ligands. Issue 11 (4th February 2016) - Farrell, Kevin; Melle, Philipp; Gossage, Robert A.; Müller-Bunz, Helge; Albrecht, Martin
Abstract : Rhodium(iii ) complexes with abnormal dicarbene and diimine ligands are transfer hydrogenation catalysts with visually distinct active and dormant states. Abstract : Treatment of an abnormal dicarbene ligated rhodium(iii ) dimer with 2, 2′-bipyridine (bipy), 1, 10-phenanthroline (phen) or 2, 2′:6′, 2′′-terpyridine (terpy) results in coordination of the N -donor ligands and concomitant cleavage of the dimeric structure. Depending on the denticity of the pyridyl ligand, this situation retains one (L = terpy) or two (L = bipy, phen) flexible sites for substrate coordination. In the case of the bipy complexes, modification of the electron density at Rh, without directly affecting the steric environment about the metal centre, was achieved by the incorporation of electron-donating or electron-withdrawing substituents on the bipy backbone. The dicarbene pyridyl complexes were active in transfer hydrogenation catalysis of benzophenone at 0.15 mol% catalyst loading in a iPrOH/KOH mixture. The catalysts displayed a strong characteristic colour change (yellow to purple) after activation which allowed for visual monitoring of the status of the reaction. The colour probe and the robustness of the active catalysts proved useful for catalyst recycling. The catalytic activity sustained over five consecutive substrate batch additions and gave a maximum overall turnover number of 3100.